Exploring the interaction between approach-avoidance conflict and memory processing. Issue 1 (2nd January 2020) - Chu, Sonja; Thavabalasingam, Sathesan; Hamel, Laurie; Aashat, Supreet; Tay, Jonathan; Ito, Rutsuko; Lee, Andy C. H.
ABSTRACT: The medial temporal lobe (MTL) has been implicated in approach-avoidance (AA) conflict processing, which arises when a stimulus is imbued with both positive and negative valences. Notably, since the MTL has been traditionally viewed as a mnemonic brain region, a pertinent question is how AA conflict and memory processing interact with each other behaviourally. We conducted two behavioural experiments to examine whether increased AA conflict processing has a significant impact on incidental mnemonic encoding and inferential reasoning. In Experiment 1, participants first completed a reward and punishment AA task and were subsequently administered a surprise recognition memory test for stimuli that were presented during high and no AA conflict trials. In Experiment 2, participants completed a reward and punishment task in which they learned the valences of objects presented in pairs (AB, BC pairs). Next, we assessed their ability to integrate information across these pairs (infer A-C relationships) and examined whether inferential reasoning was more challenging across objects with conflicting compared to non-conflicting incentive values. We observed that increased motivational conflict did not significantly impact encoding or inferential reasoning. Potential explanations for these findings are considered, including the possibility that AA conflict and memory processing are not necessarily intertwined behaviourally.